(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Childhood obesity has become a major public health challenge in developing countries including India due to the changes in the lifestyle and food habits of children owing to the influence of urban culture and technological growth. The present study is a cross-sectional, school-based study conducted to assess the prevalence of obesity and to determine the demographic variables influencing the obesity among school children.